Impact of pre-operative weight loss on non-alcoholic fatty liver disease histopathology and insulin resistance in individuals undergoing bariatric surgery: a propensity matched cross-sectional comparison - Maldonado, Fábio Henrique Ribeiro; Mega, Paulo Ferreira; Germano, Carlos Wustemberg; Dias, Luana Leite Castilho; Callejas, Guilherme Hoverter; Gestic, Martinho Antonio; Utrini, Murillo Pimentel; Chaim, Felipe David Mendonça; Callejas-Neto, Francisco; Chaim, Elinton Adami; Cazzo, Everton (São Paulo Medical Journal, 2025)
BACKGROUND: The effect of weight loss (WL) on histopathological aspects of non-alcoholic fatty liver disease (NAFLD) may provide further insights into the dynamics of hepatic recovery after WL. OBJECTIVE: To analyze the effects of pre-operative WL on insulin resistance- and NAFLD-related histology in individuals undergoing bariatric surgery (BS) with or without pre-operative WL. DESIGN AND SETTING: A matched cross-sectional study was conducted at a public university hospital and a private clinic in Campinas, Brazil. METHODS: An analytical, observational, cross-sectional study was conducted using prospectively collected databases of individuals who underwent BS and liver biopsy at either a public tertiary university hospital (with pre-operative WL) or a private clinic (without pre-operative WL). Random electronic matching by gender, age, and body mass index (BMI) was performed and two paired groups of 24 individuals each were selected. RESULTS: Of the 48 participants, 75% were female. The mean age was 37.4 ± 9.6. The mean BMI was 38.9 ± 2.6 kg/m2. Fibrosis was the most common histopathological abnormality (91.7%). Glucose was significantly lower in the WL group (92 ± 19.1 versus 111.8 ± 35.4 mg/dL; P = 0.02). Significantly lower frequencies of macrovesicular steatosis (58.3% versus 95.8%; P = 0.004), microvesicular steatosis (12.5% versus 87.5%; P < 0.001), and portal inflammation (50% versus 87.5%; P = 0.011) were observed in the WL group. CONCLUSION: Pre-operative WL was significantly associated with lower frequencies of macro- and microvesicular steatosis, portal inflammation, and lower glycemia, indicating an association between the recent trajectory of body weight and histological aspects of NAFLD.